The Firm-Level and Aggregate Effects of Corporate Payout Policy - Stylianos Asimakopoulos; James Malley; Apostolis Philippopoulos (CESifo GmbH, 2024)
This paper presents a novel study on the significance of corporate payout policy in shaping firms' financial decision-making and, in turn, the macroeconomy. To this end, we add to the literature by allowing households and firms to choose share buybacks optimally. We then explore the implications of various shocks commonly facing them, such as dividend income, investment, and tax shocks. The latter include corporate income, capital gains, and dividend income taxes. We find that the model predictions cohere well with the data when applying the non-policy shocks. We also find that tax reform's aggregate and welfare effects are overstated when share buybacks are not optimally chosen as assumed in the relevant literature.
Keywords: C68; E62; G30; G35; H25; H30; 330; dividends; share repurchases; tax reforms; payout flexibility